FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PEMBERANTASAN SARANG NYAMUK DI LINGKUNGAN TANJUNG REJO MEDAN SUNGGAL - Astuti Rofida; Resmi Pangaribuan; Khairunnisa Batubara (Universitas Pahlawan, 2021)
Dengue Hemorrhagic Fever is a viral disease carried by mosquitoes and usually occurs in tropical and subtropical areas. A person infected with this virus for the second time has a much greater risk of severe illness. Symptoms can include fever, rash, and muscles and joints. In severe cases, bleeding and shock can be life-threatening. Handling can be done by giving adequate fluids and pain relievers. Severe cases must be hospitalized. Tanjung Rejo village is one of the dengue endemic villages in Medan Sunggal sub-district. One of the most appropriate efforts in preventing and eradicating mosquitoes is by eradicating mosquito nests. The purpose of this study was to determine the factors that influence the practice of eradicating mosquito nests in the Tanjung Rejo Village, Medan Sunggal District. This type of research is Explantory Research with research population of 451 people and the number of samples is 82 people. This research instrument using a questionnaire with analysis using the chi-sguare statistical test with a degree of significance (Î±) = 0.01. The results showed that there was a relationship between knowledge (p = 0.000), attitude (p = 0.000) education (p = 0.275), occupation (p = 0.572), support from health workers (p = 0.000), and family support (p = 0.000), the results of the multivariate show that the p-value is 0.00 <0.01 then there is an influence on the practice of eradicating mosquito nests in the Tanjung Rejo environment, Medan Sunggal. Suggestions for the community to further improve the practice of eradicating dengue mosquito nests, and for health workers to send information continuously and continuously.